Young women's stroke etiology differs from that in young men: an analysis of 511 patients - Emily Nakagawa; Michael Hoffmann (MDPI AG, 2013)
Women are known to have particular heterogeneity in stroke etiology related to childbearing and hormonal factors. Although there are continued acute stroke treatment advances focusing on clot dissolution or extraction, effective secondary prevention of stroke, however, is dependent on an accurate etiological determination of the stroke. Otherwise, more strokes are likely to follow. Analysis of young women's stroke etiology in a large stroke registry incorporating contemporary neurovascular and parenchymal imaging and cardiac imaging. Young people (18-49 years old) with stroke were consecutively accrued over a 4 year period and an investigative protocol prospectively applied that incorporated multimodality magnetic resonance imaging, angiography, cardiac echo and stroke relevant blood investigations. All patients were classified according to an expanded Trial of Org 10172 in Acute Stroke Treatment − TOAST − classification and neurological deficit by the National Institute of Health stroke admission scores. In 511 registry derived, young stroke patients (mean age 39.8 years, 95% confidence interval: 39.1; 40.7 years), gender (women n=269, 53%) the etiological categories (women; men) included: i) small vessel disease (30/55;25/55), ii) cardioembolic (16/42;26/42), iii) large vessel cervical and intracranial disease (24/43;19/43), the other category (132/226; 91/226), which included, iv) substance abuse (15/41; 26/41, 4.6), v) prothrombotic states (22/37;15/37), vi) dissection (11/30;19/30), vii) cerebral venous thrombosis (15/19; 4/19, 12.4), viii) vasculitis (8/12; 4/12), ix) migraine related (10/11, 1/11) and x) miscellaneous vasculopathy (38/52;14/52). The latter entities comprised of aortic arch atheroma, vessel redundancy syndrome, vertebrobasilar hypoplasia, arterial fenestrations and dolichoectasia. Some conditions occurred solely in women, such as eclampsia (5), Call Fleming syndrome (4), fibromuscular dysplasia (3) and Moya Moya syndrome (2). Categories aside from bland infarction included: ii) intracerebral hemorrhage (43/106; 63/106) and xiii) stroke of undetermined etiology (6/10; 4/10). Admission mean National Institute of Health Stroke Scale scores differed significantly between women and men (4.7; 6.0 t=1.8, P=0.03). Young women's stroke is significantly different from men in 7/12 stroke etiological categories in addition to 4 unique subtypes that require specific management.